FRI0066 Behavior of the multi-biomarker disease activity (vectra da algorithm) score and components in patients with rheumatoid arthritis treated with tocilizumab. (23rd January 2014) - Hanami, K.; Hirata, S.; Tasaka, H.; Li, W.; Bolce, R.; Sasso, E. H.; Defranoux, N. A.; Yamaoka, K.; Saito, K.; Tanaka, Y.
Abstract : Background: The multi-biomarker disease activity (MBDA) score is a novel test that measures 12 biomarkers in serum to assess disease activity in patients with rheumatoid arthritis (RA). We previously reported the changes in MBDA score in patients treated with TNF inhibitors. TCZ has been shown to inhibit disease activity as assessed by DAS28 and CDAI. Objectives: In this study we proposed to examine the impact of TCZ on the MBDA score and its individual components in RA treated patients. Methods: The study was conducted at UOEH, Kitakyushu, Japan, on 52 RA patients who had received TCZ 8mg/kg every 4 weeks for at least 1 year. Clinical disease activity and serum biomarkers were assessed at BL, week 24 and week 52 in all patients with the exception that at week 24 MBDA was assessed in 46 patients only. Concentrations of VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, YKL-40, MMP-1, MMP-3, leptin, resistin, SAA and CRP were measured using a multiplex immunoassay and the MBDA score (1-100) was calculated using the validated Vectra™ DA algorithm [1 ]. Correlations between MBDA score and other clinical disease activity indices (DAS28-ESR, DAS28-CRP, CDAI and SDAI) were examined using Spearman's rank correlation. Median percentage changes from BL to week 24 and 52 were assessed for each individual biomarker. Results: At baseline, patients had mean (± SD) age and disease duration of 56.6±18.2 and 12.4±11.2 years respectively. Of the 52 patients studied, 29 (55.8%) received concomitant MTX; 21 (40.4%) were previously biologic naïve. At week 52 median (± SD) DAS28-ESR had decreased from 5.6 ± 1.3 at BL to 2.6 ± 1.1 (-53.1%), CDAI from 22.2 ± 12.2 to 5.6 ± 4.1 (-70.6%), and MBDA score from 57.7± 19.2 to 42.5 ±16.2 (-16.5%). MBDA scores at BL correlated significantly with DAS28-ESR (r=0.54 p<0.001), CDAI (r=0.31, p=0.0245) and SDAI (r=0.45, p=0.009). Changes in MBDA from BL to week 52 also correlated with those of DAS28-ESR (r=0.47, p<0.001) and CDAI (r=0.37, p=0.007). Most of the 12 biomarkers were suppressed with TCZ. By contrast median IL-6 concentration increased from BL to week 24 and 52 with median percent changes (IQR) of +29% (-41, +380) and +24% (-65, +320) respectively. Conclusions: A decrease in MBDA scores in patients treated with TCZ was observed and correlated with changes in disease activity as measured by DAS28-ESR and CDAI. However, TCZ treatment led to smaller median percentage changes in MBDA score, compared with DAS28-ESR and CDAI scores. Median serum concentrations of all individual components of the MBDA score decreased to the exception of IL-6 which increased. References: Curtis JR, et al., Validation of a novel multi-biomarker test to assess rheumatoid arthritis disease activity. Arthritis Care & Research 2012; 64(12):1794 Disclosure of Interest: K. Hanami: None Declared, S. Hirata: None Declared, H. Tasaka: None Declared, W. Li Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., R. Bolce Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., E. Sasso: None Declared, N. Defranoux Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., K. Yamaoka Consultant for: Pfizer, Chugai Pharmaceutical Co. Ltd, K. Saito: None Declared, Y. Tanaka Grant/research support from: Bristol-Myers Squibb, MSD K.K., Chugai Pharma Co., Ltd., Mitsubishi-Tanabe Pharma Co., Ltd., Astellas Pharma Inc., Abbott Japan Co., Ltd., Eisai Co., Ltd. and Janssen Pharmaceutical K.K., Speakers bureau: Mitsubishi-Tanabe Pharma Co., Ltd., Abbott Japan Co., Ltd., Eisai Co., Ltd., Chugai Pharma Co., Ltd., Janssen Pharma K.K., Santen Pharma Co., Ltd., Pfizer Japan Inc., Astellas Pharma Inc., Daiichi-Sankyo Co., Ltd., GlaxoSmithKline K.K., Astra-Zeneca, Otsuka Pharma Co., Ltd., Actelion Pharma Japan Ltd., Eli Lilly Japan K.K., Nippon Kayaku Co., Ltd., UCB Japan Co., Ltd., Quintiles Transnational Japan Co. Ltd., Ono Pharma Co., Ltd.